The effect of the orientational anisotropy of VCSEL parameters on the possibility to implement polarization switching - Burov, Leonid I.; Gorbatsevich, Alexander S.; Lobatsevich, Pavel M. (Journal of the Belarusian State University. Physics, 2018)
Based on the results of numerical simulation, orientational anisotropy effects of the spontaneous emission factor, mirror reflectivity, and internal losses on the polarization switching (PS) behavior of surface-emitting semiconductor lasers (VCSEL) have been studied. It has been shown that actually the orientational anisotropy of a spontaneous emission factor has no effect on PS parameters, though even minor anisotropy of the mirror reflectivity can lead to a substantial shift of the PS point. The internal loss orientational anisotropy is liable to increase the amplification anisotropy effects as well as to compete with them, changing not only the PS point position but also the limiting stationary values of a polarization degree.